Community-Based Entrepreneurship Development for Sustainable Ecotourism: A Case Study in Bogor Regency, Indonesia - Sariat Arifia; Ermiani; Beti Renitawati; Zisca Marcellina Mukti (Research Synergy Foundation, 2025)
Rural areas often face socioeconomic and environmental challenges, including limited economic opportunities and the degradation of natural resources, which necessitate sustainable development models. This study addresses this critical issue by examining the potential, impacts, and optimization of community-based Ecotourism for sustainable development in selected sites in Bogor Regency, Indonesia. Using a qualitative approach and a multiple-case study method, the research revealed that community-based Ecotourism enhanced local economic welfare by diversifying income sources, creating job opportunities, and fostering entrepreneurial activities through ticket sales, guide services, and local product marketing. Further, it contributed to social welfare by empowering local communities, strengthening social cohesion, and supporting community-led initiatives such as interest-free loans and disaster relief programs. Environmental benefits were observed by consistently applying sustainable practices, including effective waste management and biodiversity conservation. Despite these gains, the study identified critical challenges: the need for improved infrastructure, enhanced governmental support, and ongoing capacity building for local stakeholders. Unlike previous studies, this research advances the literature by integrating economic, social, and environmental dimensions into a unified framework for sustainable Ecotourism, offering valuable implications for policymakers and practitioners in rural tourism development.